A serial mediation model of negative life events on school adjustment of left-behind children in rural China: the central role of teacher support and positive emotions - Jiang, Yuqin; Zhang, Lyuci; Roslan, Samsilah; Zaremohzzabieh, Zeinab; Govindasamy, Priyalatha; Mohd Isa, Nor Junainah; Che Amat, Muhammad Asyraf; Puad Mohd Kari, Dharatun Nissa; Du, Lifeng (John Wiley and Sons, 2025)
Left-behind children in China face increasing challenges in school adjustment due to the complex interaction between negative life events (NLEs), social support systems, and the educational environment. This study aimed to explore the relationships among NLEs, teacher support, positive emotions, and school adjustment, and to determine whether teacher support and positive emotions mediate the effect of NLEs on school adjustment. A questionnaire survey was conducted among 678 junior high school students (317 boys, 361 girls, M_age = 15 years) in Guangxi Province. A serial mediation model was used to examine the mediating roles of teacher support and positive emotions. The findings indicate that teacher support and positive emotions play a significant mediating role in the relationship between NLEs and school adjustment, indicating that enhancing teacher support and fostering positive emotions can mitigate the negative effects of NLEs. These findings underscore the importance of a supportive educational environment and provide practical implications for interventions aimed at improving the well-being and school adjustment of left-behind children.